The Late Permian tetrapod ichnoassociation from Italy - Marchetti, Lorenzo; Ceoloni, Paola; Leonardi, Giuseppe; Massari, Francesco; Mietto, Paolo; Sacchi, Eva; Valentini, Mara (Journal of Mediterranean Earth Sciences, 2020)
The tetrapod footprints from the Late Permian of Italy are worldwide known and were the subject of a number of studies. They come mostly from the Dolomites and especially from the Bletterbach gorge, other occurrences are known from the Venetian Prealps and the Carnian Alps. The track-bearing unit is the alluvial and marginal marine Arenaria di Val Gardena Formation, deposited under a semi-arid climate during the late Lopingian. In the last comprehensive revision, the tetrapod ichnoassociation includes abundant and diverse eureptile tracks (cf. Dromopus, Rhynchosauroides, Paradoxichnium, cf. Protochirotherium), abundant parareptile tracks (Procolophonichnium, Pachypes), uncommon but diverse therapsid tracks (Capitosauroides, Dicynodontipus, Dolomitipes) and rare anamniote tracks (cf. Batrachichnus). The occurrence of further ichnotaxa, such as Contiichnus and Merifontichnus, is currently debated. This is the most abundant, diverse and best-preserved tetrapod ichnoassociation of the Late Permian all over the world, thus it is a reference for tetrapod ichnotaxonomy. It is characterized by a strong Triassic affinity and includes the earliest evidence of an archosauriform radiation and some of the earliest clues of parasagittal locomotion. This low-latitude tetrapod ichnoassociation is similar to contemporary faunas from mid- and high-palaeolatitudes, but it seems to be more diverse, thus suggesting higher origination rates and lower extinction rates. In tetrapod footprint biochronology, it is currently the reference for the Bletterbach Ichnofaunal Unit and the Paradoxichnium tetrapod footprint biochron. Also, it may include the base of the Protochirotherium tetrapod footprint biochron.